A conceptual model for understanding the rapid COVID-19–related increase in food insecurity and its impact on health and healthcare. Issue 5 (7th August 2020) - Leddy, Anna M; Weiser, Sheri D; Palar, Kartika; Seligman, Hilary
ABSTRACT: Food insecurity, a well-established determinant of chronic disease morbidity and mortality, is rapidly increasing due to the coronavirus disease 2019 (COVID-19) pandemic. We present a conceptual model to understand the multiple mechanisms through which the economic and public health crises sparked by COVID-19 might increase food insecurity and contribute to poor health outcomes in the short- and long-term. We hypothesize that, in the short-term, increased food insecurity, household economic disruption, household stress, and interruptions in healthcare will contribute to acute chronic disease complications. However, the impact of the pandemic on food security will linger after social-distancing policies are lifted and the health system stabilizes, resulting in increased risk for chronic disease development, morbidity, and mortality among food-insecure households in the long-term. Research is needed to examine the impact of the pandemic-related increase in food insecurity on short- and long-term chronic health outcomes, and to delineate the underlying causal mechanisms. Such research is critical to inform the development of effective programs and policies to address food insecurity and its downstream health impacts during COVID-19 and future pandemics.